Promosi Literasi Antibiotik Sejak Dini melalui Media Infografis dan Komik pada Siswa Sekolah Dasar - Ikhwan Yuda Kusuma; Supriani Supriani; Fiqih Nurkholis; Septi Nurkhasanah; Afriza Pujiati; Khaniva Khalilia Alazhar (Daarul Ilmi: Jurnal Pengabdian Kepada Masyarakat, 2025)
Introduction: Irrational use of antibiotics remains a major global and national public health challenge, contributing to the accelerating problem of antimicrobial resistance. Low antibiotic literacy is a key determinant of inappropriate antibiotic use, and misconceptions often develop from an early age due to limited health education. Therefore, promotive and preventive educational strategies targeting children are essential to foster appropriate antibiotic use and long-term behavioral change. Objective: The purpose of this community service activity was to promote and improve antibiotic literacy among elementary school students through the use of infographic and comic-based educational media. Method: This community service activity was conducted using a qualitative descriptive approach with a participatory educational design based on Participatory Action Research. The intervention employed visual educational media in the form of infographics and an educational comic titled “Una and the Mission to Finish Antibiotics.” Data were collected through participatory observation, interactive discussions, and simple written interviews, and analyzed using thematic analysis. Result: The activity revealed three main response patterns among students: positive responses characterized by a clear understanding of antibiotic use and the importance of completing therapy, partial responses indicating basic understanding but conceptual confusion, and limited responses reflecting minimal comprehension. Most students demonstrated high engagement and increased awareness of appropriate antibiotic use. Conclusion: Infographic and comic-based education is an effective and child-appropriate strategy for promoting early antibiotic literacy. This approach supports preventive efforts in pharmaceutical and public health education and has strong potential to encourage rational antibiotic use when integrated into school-based learning.